2016
DOI: 10.7863/ultra.16.03068
|View full text |Cite|
|
Sign up to set email alerts
|

Implementation of a 4‐Year Point‐of‐Care Ultrasound Curriculum in a Liaison Committee on Medical Education–Accredited US Medical School

Abstract: Objectives-The established benefits of point-of-care ultrasound have given rise to multiple new and innovative curriculums to incorporate ultrasound teaching into medical education. This study sought to measure the educational success of a comprehensive and integrated 4-year point-of-care ultrasound curriculum.Methods-We integrated a curriculum consisting of traditional didactics combined with asynchronous learning modules and hands-on practice on live models with skilled sonographers into all 4 years of educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 20 publications
1
31
0
1
Order By: Relevance
“…Ultrasound curricula have been formalized in 28% of medical schools, with longitudinal implementation described through workshops within the preclinical years and electives or clinical tracks in the senior years . At Yale School of Medicine (YSM), we have been piloting POCUS teaching to a proportion of medical students with emphasis on using a small‐group format during regular biweekly bedside tutorials.…”
mentioning
confidence: 99%
“…Ultrasound curricula have been formalized in 28% of medical schools, with longitudinal implementation described through workshops within the preclinical years and electives or clinical tracks in the senior years . At Yale School of Medicine (YSM), we have been piloting POCUS teaching to a proportion of medical students with emphasis on using a small‐group format during regular biweekly bedside tutorials.…”
mentioning
confidence: 99%
“…This review found that between studies, there was significant variability in how long students were granted access to the use of ultrasound machines. The study authors also indicated that these programs were also feasible and could be practically implemented (Rempell et al, 2016;Wilson et al, 2017). Students reported that they enjoyed the practical component of imaging courses and often indicated in feedback that they would have preferred additional time to use the ultrasound machines.…”
Section: Discussionmentioning
confidence: 88%
“…Wilson et al, 2017 Yes-multiple didactic learning sessions over a structured four year course. Wilson et al, 2017 Yes-multiple didactic learning sessions over a structured four year course.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations